The Characteristics of Transformative Leadership in Islamic Education Institutions - Suprihno; Eti Rohmawati (Tarbiyah Departement collaboration with AMCA, 2019)
Transformative leaders are leaders who bring a change to the members and the environment. In this study is intended to describe the characteristics of transformative leadership in Islamic educational institutions. The method used is qualitative research. The data obtained is from the results of library research. Data analysis is done step by step: data presentation, data filtering, classification and drawing conclusion. The results of the study can be summarized as follows: There are several characters of transformative leaders based Umar Bin Khattab they are; Wira'i; the patient and optimism; the master of archery; smart; clever and nimble; meticulous; Hard worker and etc. There are several characteristics in transformational leadership in Islamic education is a reflection of charismatic leaders such as Idealized Influence (II), Inspirational Motivation (IM), Intellectual Stimulation (IS), Individualized Consideration (IC), Contingent Reward (CR), Manage by Exception (MBE) and Laissez-Faire Leadership (LF)